2020
DOI: 10.1016/j.jagp.2020.05.028
|View full text |Cite
|
Sign up to set email alerts
|

(Vi)-rushed Into Online Group Schema Therapy Based Day-Treatment for Older Adults by the COVID-19 Outbreak in the Netherlands

Abstract: Background: Societal measures in context of the COVID-19 outbreak forced us to transform our schema therapy based day-treatment for older adults with chronic affective disorders and personality problems into an online program. The objective of this paper is to present first impressions of this transformation. Methods: Using over-the-phone instructions initially, all patients were able to participate with the online therapy program. To reduce screen-time for patients, the nonverbal therapies were shortened. Fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 9 publications
1
33
0
4
Order By: Relevance
“…The use of technology to protect and improve mental health [ 179 ] and to maintain the health and independence [ 180 ] of older adults during this crisis was also discussed. The transformation of an on-site program into an online program for older populations [ 181 ] was found to be effective. Innovative programs should therefore be created with the goal of supporting vulnerable older adults and minimizing the long-term consequences and feelings of loneliness.…”
Section: Discussionmentioning
confidence: 99%
“…The use of technology to protect and improve mental health [ 179 ] and to maintain the health and independence [ 180 ] of older adults during this crisis was also discussed. The transformation of an on-site program into an online program for older populations [ 181 ] was found to be effective. Innovative programs should therefore be created with the goal of supporting vulnerable older adults and minimizing the long-term consequences and feelings of loneliness.…”
Section: Discussionmentioning
confidence: 99%
“…Van Dijk et al assessed maintaining a telephone conversation program in a sample of older adults with chronic affective disorders. This study showed positive results in this group, especially in relation to the development of resilience and adaptation to the new phase [ 20 ]. Another study by Wei et al performed an internet-based intervention for relaxation and self-care, and found that patients exhibited significantly decreased levels of depression and anxiety symptoms vs. those in the control group during the COVID-19 pandemic [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…can be trained as a self-regulation technique, W.A.R.A.’s more frequent practice might improve stress-resilience in vulnerable patients. For more extended online therapies such as Online Group Schema Therapy Based Day-Treatment ( van Dijk et al, 2020 ), W.A.R.A. remote therapy could be a welcome addition to teach patients with negative affect self-regulation.…”
Section: Discussionmentioning
confidence: 99%